Dyscalculia – a cognitive approach - Johnsen, Fritz (NOMAD Nordic Studies in Mathematics Education, 2004)
47 students ranging in age from 8 to 16 years have been evaluated for mathematical disabilities. This study shows an indication of certain patterns to be found in the test results. The basic cognitive production involved in solving mathematical problems displays a varied picture, involving executive functions, sequential and simultaneous processing, arousal/attention areas, automation, and cognitive integration. The results from the assessments are discussed from a cognitive point of view.